16 Impaired strain precedes fibrosis in lamin heart disease. (28th January 2023) - Topriceanu, Constantin-Cristian; Topriceanu, Constantin-Cristian; Al-Farih, Mashael; Ilie-Ablachim, Denis C; Webber, Matt; Joy, George; Pettit, Stephen; O'Brien, Ben; Hughes, Alun D; Savvatis, Konstantinos; Mohiddin, Saidi; Moody, William; et al.
Abstract : Introduction: LMNA gene mutations encoding nuclear envelope proteins Lamins A/C cause serious lamin heart disease characterized by conduction abnormalities, left ventricular (LV) dysfunction and high risk of sudden cardiac death. We used cardiovascular magnetic resonance (CMR) to understand the relationship between myocardial deformation and fibrosis in patients with lamin heart disease. Materials and Methods: This prospective multi-centre study (REC: 17/LO/0167; NCT03860454 ) recruited 20 patients with confirmed pathogenic LMNA gene mutations ( LMNA+ ) (44.9±17.47yrs, 8% male) and 20 controls (37.00 ± 13.27yrs, 55% male). Participants underwent CMR to obtain: LV ejection fraction (LVEF), LV mass, myocardial contraction fraction (MCF), LV regional wall thickening, left atrial (LA) area, 3-dimensional feature tracking strain parameters (radial, circumferential, longitudinal peak strain, systolic and diastolic rates [PS/PSSR/PDSR]), and volume of late gadolinium enhancement (LGE). CMR analysis was done in cmr42, group comparisons were done using Mann-Whitney U-test and LGE patterns were clustered using Gaussian mixture models (GMM). 95% confidence intervals (CI) of estimates were derived using adjusted bootstrap percentile method. Results: Compared to controls, LMNA+ had lower LVEF (50.9% [95% CI: 39.9, 51.4] vs 59.9% [59.4, 65.4], p <0.0001), lower MCF (0.89 [0.94, 1.10] vs 0.97 [0.88, 1.01], p =0.008), larger LA (22.2cm 2 [21.0, 23.5] vs 19.2cm 2 [18.8, 20.9], p =0.024), and more LGE in all 16 cardiac segments (all p <0.05). Generally, LMNA + had poorer radial and circumferential PS/PSSR/PDSR when compared to controls, especially in the septum, and even in segments free of LGE ( figure 1 ). Amongst LMNA+ with LGE (n=14, 70%), two distinct clusters emerged: patients with midwall septal LGE and those with non-septal LGE ( figure 2 ). Impaired strain tracked closely with LGE volume in non-septal segments, while strain parameters were better conserved in areas of midwall septal LGE ( figure 3 ). Discussion: Midwall septal fibrosis is common but not ubiquitous in lamin heart disease, and in this cohort fibrosis away from the septum appears to be more detrimental for regional mechanics. Impaired strain profiles were observed in LMNA+ patients free of LGE. The use of strain as an early pre-fibrosis biomarker warrants further investigation. Conclusion: Midwall septal fibrosis might be a distinct phenotype in lamin heart disease. Even LMNA+ patients free of LGE had impaired strain profiles. Acknowledgements: The authors would like to thank all the study participants for their participation and engagement in this study. Your contribution to science is extremely valued and appreciated.